ULF Wave Transmission Across Collisionless Shocks: 2.5D Local Hybrid Simulations. Issue 11 (9th November 2021) - Kajdič, P.; Pfau‐Kempf, Y.; Turc, L.; Dimmock, A. P.; Palmroth, M.; Takahashi, K.; Kilpua, E.; Soucek, J.; Takahashi, N.; Preisser, L.; Blanco‐Cano, X.; Trotta, D.; et al.
Abstract: We study the interaction of upstream ultralow frequency (ULF) waves with collisionless shocks by analyzing the outputs of 11 2D local hybrid simulation runs. Our simulated shocks have Alfvénic Mach numbers between 4.29 and 7.42 and their θ B N angles are 15 °, 30 °, 45 °, and 50 ° . The ULF wave foreshocks develop upstream of all of them. The wavelength and the amplitude of the upstream waves exhibit a complex dependence on the shock's M A and θ B N . The wavelength positively correlates with both parameters, with the dependence on θ B N being much stronger. The amplitude of the ULF waves is proportional to the product of the reflected beam velocity and density, which also depend on M A and θ B N . The interaction of the ULF waves with the shock causes large‐scale (several tens of upstream ion inertial lengths) shock rippling. The properties of the shock ripples are related to the ULF wave properties, namely their wavelength and amplitude. In turn, the ripples have a large impact on the ULF wave transmission across the shock because they change local shock properties ( θ B N, strength), so that different sections of the same ULF wavefront encounter shock with different characteristics. Downstream fluctuations do not resemble the upstream waves in terms the wavefront extension, orientation or their wavelength. However, some features are conserved in the Fourier spectra of downstream compressive waves that present a bump or flattening at wavelengths approximately corresponding to those of the upstream ULF waves. In the transverse downstream spectra, these features are weaker. Plain Language Summary: We address the problem of what happens to upstream ultralow frequency (ULF) waves as they reach shocks and are carried into the downstream region. We do this by analyzing the results of 11 2.5D local hybrid simulations of collisionless shocks. We find that the waves are not simply transmitted into the downstream region but that their identity is largely destroyed, as the downstream fluctuations do not resemble the upstream waves neither in wavelengths nor in appearance. However, some features observed in the Fourier spectra of upstream ULF waves are conserved in the Fourier spectra of compressive downstream fluctuations. Key Points: Upstream ultralow frequency (ULF) waves are not simply transmitted across collisionless shocks Some spectral features of compressive upstream ULF waves are conserved in the spectra of downstream fluctuations There is some correlation between the properties of the shock ripples and the foreshock ULF waves